(untitled) (Journal of Plant Disease Sciences, 2025)
Marigold (Tagetes spp.) is a widely cultivated commercial flower crop in India. In the South Gujarat region, significant damage to marigold crops has been observed due to the foliar pathogen Alternaria tenuissima, which causes leaf spot and flower blight. This study, conducted over a three-year period, aimed to evaluate the efficacy of different fungicidal treatments for managing this disease.Results showed that three foliar sprays of either hexaconazole 4% + zineb 68% WP (0.072%, i.e., 1g/lit), mancozeb 75WP (0.225%, i.e., 3g/lit), or tebuconazole 50% + trifloxystrobin 25% WG (0.03%, i.e., 0.4g/lit) were effective in controlling leaf and flower blight. Sprays were applied at the onset of disease, followed by two subsequent sprays at 15-day intervals.Among the treatments, hexaconazole 4 + zineb 68 WP showed the highest Incremental Cost-Benefit Ratio (ICBR) of 1:4.73, followed by mancozeb 75WP (ICBR 1:4.32) and tebuconazole 50 + trifloxystrobin 25WG (ICBR 1:3.87). In addition to effective disease control, these treatments also enhanced flower yield and were found to be non-phytotoxic to the plants and flowers.